The Effect of Laser Setting on Engraving Results of A CNC Laser Engraver Machine - Anrinal Anrinal; Farza Anugrah Pratama; Asmara Yanto (Jurnal Teknik Mesin, 2023)
This research aims to determine the effect of laser settings on the engraving results of a CNC Laser Engraving machine on plywood media. Controlling the movement of the CNC laser machine spindle using Arduino UNO. Testing was carried out by setting the laser power (S-Max) scales are 100, 200, 300, 400, 500 and 600. Position variations of laser head above the plywood media are 3 cm, 5 cm and 7 cm. The test results show that low S-Max scale will produce unclear dotted lines if graving the circle shape and the greater S-Max scale, the thicker the line will be. The lower position of the laser head above the surface of the plywood media, the wider the graving size (engraving line width). The best engraving results were obtained with S-Max scale is 400 and position of laser head above the plywood media is 5 cm with fairly stable and clear engraving lines.